March: Book One - Lewis, John, 1940-2020.; Aydin, Andrew; Powell, Nate; Small Press Expo Collection (Library of Congress) (Marietta, GA : Top Shelf Productions, 2013)
This graphic novel is Congressman John Lewis' first-hand account of his lifelong struggle for civil and human rights, meditating in the modern age on the distance traveled since the days of Jim Crow and segregation. Rooted in Lewis' personal story, it also reflects on the highs and lows of the broader civil rights movement. Book One spans Lewis' youth in rural Alabama, his life-changing meeting with Martin Luther King, Jr., the birth of the Nashville Student Movement, and their battle to tear down segregation through nonviolent lunch counter sit-ins, building to a climax on the steps of City Hall. His commitment to justice and nonviolence has taken him from an Alabama sharecropper's farm to the halls of Congress, from a segregated schoolroom to the 1963 March on Washington D.C., and from receiving beatings from state troopers, to receiving the Medal of Freedom awarded to him by Barack Obama, the first African-American president.
"March is a vivid first-hand account of John Lewis' lifelong struggle for civil and human rights, meditating in the modern age on the distance traveled since the days of Jim Crow and segregation. Rooted in Lewis' personal story, it also reflects on the highs and lows of the broader civil rights movement."--Back cover flap.
Accelerated Reader AR
Coretta Scott King Author Honor, 2014
Accelerated Reader
Keywords: Lewis, John, -- 1940-2020 -- Cartoons and comics; Lewis, John, -- 1940 February 21- -- Comic books, strips, etc; Civil rights movements -- United States -- Comic books, strips, etc; African American civil rights workers -- Biography -- Cartoons and comics; Civil rights movement -- United States -- Cartoons and comics; Cartoons and comics; Graphic novels; Civil rights movements; United States; African American civil rights workers -- Comic books, strips, etc; Legislators -- United States -- Comic books, strips, etc; African American legislators -- Comic books, strips, etc; Civil rights movements -- History -- Comic books, strips, etc; Comic books, strips, etc; African Americans -- Civil rights -- Comic books, strips, etc; Civil rights workers -- Comic books, strips, etc; Coretta Scott King honor books; Biographical comics; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Historical comics; Nonfiction comics; Biographical comics; Historical comics; Nonfiction comics; Comics (Graphic works); Graphic novels; Comics (Graphic works); Comic books, strips, etc; Graphic novels; Coretta Scott King Award (author) -- Honor book -- 2014.; Comic books, strips, etc; Autobiographical comics